A multi-proxy reconstruction of Late Cretaceous climate - O'Connor, LK (2018)
The Late Cretaceous (100.5–66.0 Ma) was a greenhouse world with high atmospheric CO2, which fluctuated on long and short timescales, that can provide insights into how Earth’s climate system operates under different CO2 levels to today. This thesis applies a multi-proxy approach to reconstructing palaeoclimate through the collapse of the Late Cretaceous greenhouse, at tectonic to sub-orbital timescales, with the goal of disentangling CO2 from other climatic drivers. This thesis demonstrates that, although atmospheric CO2 was a dominant driver, local sea-surface temperature, sedimentation patterns, and water chemistry were influenced by changing circulation and orbital forcing on a range of timescales.